Peritoneal mesothelioma in Sweden: A population‐based study. (4th September 2019) - Cashin, Peter H.; Jansson Palmer, Gabriella; Asplund, Dan; Graf, Wilhelm; Syk, Ingvar
Abstract: The study aim was to report survival and morbidity of all patients in Sweden with peritoneal mesothelioma treated with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) as well as investigate whether the survival has increased on a population level since this treatment was nationalized 2011. Study data were collected from the Swedish HIPEC registry and the Swedish National Cancer Registry. All patients with peritoneal mesothelioma scheduled for CRS/HIPEC treatment in Sweden January 2011 to March 2018 were retrieved from the Swedish HIPEC registry. Clinicopathological and survival data were collected. For population‐level analysis, all patients with diffuse malignant peritoneal mesothelioma (DMPM) were identified from the Swedish National Cancer Registry and data were retrieved from two separate 5‐year time periods: 1999‐2003 and 2011‐2015. Thirty‐two patients were accepted for CRS/HIPEC. Four were open/close cases. Two‐year survival rate was 84% or 59% when excluding borderline peritoneal mesotheliomas (n = 17). Median overall survival was not reached. Grade III‐IV Clavien‐Dindo events occurred in 22% with no mortality. From the national cancer registry, 102 DMPM cases were retrieved: 40 cases between 1999 and 2003, and 62 cases between 2011 and 2015 (corresponding to an increase from 0.9 to 1.24/million/year, P = .04). Six patients (10%) received CRS/HIPEC in the second period. Median OS increased between periods from 7 to 15 months and 5‐year survival from 14% to 29% ( P = .03). Peritoneal mesothelioma of both borderline and DMPM subtypes undergoing CRS/HIPEC have good long‐term survival. The incidence of DMPM in Sweden has increased. Overall survival has increased alongside the introduction of CRS/HIPEC, which may be a contributing factor. Abstract : Peritoneal mesothelioma of both borderline and malignant subtypes can be successfully managed with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. The incidence of diffuse malignant peritoneal mesothelioma has statistically increased over time in Sweden; fortunately likewise, the overall survival has also increased statistically in part due to the implementation of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy.